2016
DOI: 10.1007/s12288-016-0696-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heart and Liver Iron Overload in Thalassemia Major Patients Using T2* Magnetic Resonance Imaging

Abstract: Accumulation of excess iron in heart can lead to cardiac dysfunction, which is the most common cause of death in thalassemia major patients. Biopsy is an invasive procedure and therefore not an ideal option to assess iron load. However, standard/usual non-invasive methods, such as ferritin measurement, have some limitations and the results show poor correlations with iron load. Magnetic Response Imaging (MRI-T2*), as a non-invasive and reliable method for iron load assessment in organs such as liver and heart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
(30 reference statements)
2
8
0
Order By: Relevance
“…Our results demonstrated a significant correlation between liver and heart iron load assessed by MRI-T2*, while this correlation was lost at follow-up. These contradictory findings are consistent with previous reports [33,34]. These results could be attributed to differences in iron transport and deposition in these organs [33].…”
Section: Discussionsupporting
confidence: 91%
“…Our results demonstrated a significant correlation between liver and heart iron load assessed by MRI-T2*, while this correlation was lost at follow-up. These contradictory findings are consistent with previous reports [33,34]. These results could be attributed to differences in iron transport and deposition in these organs [33].…”
Section: Discussionsupporting
confidence: 91%
“…And with Wahidiyat et al (18) study that showed the magnitude of liver iron overload does not correlate with myocardial iron. In other studies, like Merchant et al (19) and Farhangi et al (21) studies no correlation was found between liver and heart iron load.…”
Section: Discussionmentioning
confidence: 81%
“…Even ageing anaemic patients with adequate ferritin levels, but in a state of chronic inflammation, may be inadvertently administered iron [16]. It is unclear whether the amount of iron administered is appropriate, but there are several reports of iron overload using MRI and liver fibrosis markers in cases of thalassemia [17,18]. Furthermore, in hepatitis C cases, associations of iron overload in liver biopsies have also been investigated [17].…”
Section: Plos Onementioning
confidence: 99%